Características do acesso aos alimentos em Erechim, Rio Grande do Sul, Brasil - Zenicléia Angelita Deggerone; Fabiane Wiederkehr; Cibele Lúcia Bombardelli (Confins)
This study intent to spatially analyze the distribution of establishments that sell food in the city of Erechim/RS, in order to verify the existence of food deserts. This is a descriptive and exploratory study that was prepared from the analysis of secondary data collected between January and February 2022 with the Secretary of Finance of the Erechim Municipality on establishments that sell food and at the Brazilian Institute of Geography and Statistics (IBGE), on family income, population and census sectors. The collected information was entered into the free geoprocessing software QGis Desktop 3.22 to perform the correlation, spatial analysis and the generation of thematic maps. The research revealed that the central regions of the Erechim city of concentrate the largest number of establishments that sell food. In peripheral regions and with low family income, there is a smaller amount of all types of establishments that sell food, especially those that sell healthy foods and hypermarkets/supermarkets. These results reveal that the food supply in the city of Erechim is unequal, which conditions the existence of food deserts. That way, it is recommended that the municipal government develop actions to promote access to more sustainable food systems.